Experience Report about the Activities in the Mackenzie Presbiterian University related to IETF, IRTF and ISOC - Braga, Julião; Omar, Nizam; Silva, Vagner (Anais do Workshop Pré-IETF (WPIETF); 2015: Anais do II Workshop Pré-IETFDO - 10.5753/wpietf.2015.10470, 2015)
This paper discusses the initiatives taken under the Mackenzie Prebisterian University with respect to IETF, IRTF and ISOC during the period 2012- 2015. Additionally, it makes an approach regarding the involvement of people of the LACNIC region in the IETF and features the low participation of regions on the in uence of AFRINIC and LACNIC. In addition we present some proposed actions to take for the next five years.